Can our Laws Save Species Like Eria meghasaniensis? - Paul, Shashi (Indian Forester, 2016)
Eria meghasaniensis is one of the endemic Orchids of Odisha with a single population of nearly 150 plants found in Simlipal area of Odisha. It needs immediate measures to ensure its recovery and survival. On examination of various provisions of the Wildlife (Protection) Act, 1972 and the Odisha Forest Act, 1972, it is seen that they are not very helpful in rehabilitation of such species. Section 38 of the Biological Diversity Act, 2002, takes care of such species. However, the mechanism in place to implement this section to its full scope needs strengthening. For this purpose the Endangered Species Act (ESA) of USA and Species At Risk Act (SARA) of Canada were examined and it is found that they have good provisions to focus on rehabilitation of species at risk and to save them from extinction. It is highly required to develop a robust mechanism to implement the provisions of section 38 of the Biological Diversity Act, 2002, by using acts like ESA and SARA as guiding features. By developing an open and transparent process, based on scientific data available, with an actionable and time bound recovery plan and with the involvement of all stakeholders, it may be possible to save species like Eria meghasaniensis from extinction.